Collection of rates - between sanction and persuasion - Alias, Buang (2003)
This paper is based on a study conducted by the author to explain reasons for the accumulation of uncollected rates or property tax in local authorities. Approaching the study from a macro perspective and using data from 69 local authorities it was found that the inability of some local authorities to collect rates is due to inefficiency, third party intervention as well as attitude of ratepayers. Focusing on the ratepayers, their reasons for not paying rates include perception of inequity in the balance of trade (higher percentage of expenditure in local authorities is towards emolument payment), level of income of ratepayers, third party influence and availability of opportunities for ratepayers to delay making payments. Added to this is lack of deterrence measures undertaken by local authorities. A blanket approach, such as appointing legal firms as collector is costly but seldom successful. What should be undertaken by local authorities is to conduct their own research to understand the thinking of rate defaulters. Here, some form of investment is needed. If reasons for non-payment are due to inadequate fund then persuasion should be the approach. However, if it was found that the rate payers is actually well off, then the deterrence approach should be adopted. As a conclusion, to address the issue of uncollected rates,local authorities should not adopt a blanket approach but rather a combination of both persuasion and deterrence. The best however is to educate ratepayers of their social responsibility and for local authority's role as coordinator in the development and management of urban areas be highlighted